Spectrophotometric detection of bacteriolytic activity of diluted lysostaphin solutions - Márová, I; Kovár, J (Folia microbiologica, 1993)
Turbidimetric method with spectrophotometric detection of changes in density of test bacteria S. aureus strain SA 812 for determination of bacteriolytic activity of lysostaphin was employed. Results of two evaluations are compared: (1) calculation of the relative value of turbidity decrease on the basis of the difference of absolute values of A540 at the beginning of reaction and after the incubation period, (2) following of time changes in A540 by monitoring the course of reaction directly in the constant-temperature cuvette of the spectrophotometer at 37 degrees C. Both arrangements yielded identical results, within the significance level of 0.05. With concentrated samples both methods yield reliable results; with diluted samples the accuracy of the "absolute" method decreases together with decreasing lysostaphin concentration much faster than with the "registration" method. The registration method makes it possible to detect even minute amounts of the lytic enzyme and thus to distinguish the values of activity in dilute samples even when data obtained by means of the "absolute" method cannot be considered as reliable. A unit of bacteriolytic activity can be expressed from the kinetic curve as an amount of enzyme preparation causing delta A540/min = 0.01.
Keywords: Fluorometry; bakteriolýza; Spectrophotometry; Staphylococcus aureus; Temperature; vztah mezi dávkou a účinkem léčiva; Dose-Response Relationship, Drug; nefelometrie a turbidimetrie; Nephelometry and Turbidimetry; spektrofotometrie; teplota; Lysostaphin; fluorometrie; Bacteriolysis; lysostafin